PENERAPAN TEKNOLOGI PEMANFAATAN CEKER AYAM BROILER MENJADI KRUPUK KULIT UNTUK HOME INDUSTRI DALAM RANGKA PEMBERDAYAAN EKONOMI MASYARAKAT DESA KELATING - IN.S. MIWADA; S.A. LINDAWATI; WIJANA WIJANA (Buletin Udayana Mengabdi, 2006)
ABSTRACT The activity of community service was carried out with tittle ? Aplication of the foot birds technology be snack food for home industry to using the economic society at Kelating village?. It was carried out at Balai Desa Kelating on 23th September 2005. This socialization aimed to demonstration of the foot birds technology be snack food. The methods of activity was demonstration with the implementation three methods doing the snack food, that is one method with added lime, two method with added baking powder and three method without lime and baking powder. Previously it is explained by the theory. The result of activity on the whole success. The participant prefer the snack food for one method and two method. It can be concluded that, the participant very enthusiastic follow application of the foot birds technology be snack food and its never before the snack food production.